Reintroducing Consciousness in Psychopathology: Review of the Literature and Conceptual Framework - Ouwersloot, Gert; Derksen, Jan; Glas, Gerrit (Frontiers in Psychology, 2020)
Alterations in consciousness are among the most common transdiagnostic psychopathological symptoms. Therefore clinical practice will benefit from a clear conceptual framework that guides recognizing, comprehending and treating consciousness disorders. However, contemporary psychopathology lacks such a framework. We describe how pathology of consciousness is addressed in clinical psychology and psychiatry so far, and how DSM-5 and ICD-10 refer to this subject. A brief review of the literature on consciousness is given. After describing psychological perspectives on consciousness and discussing theoretical issues involved in exploring consciousness, we offer a practical clinical working definition of consciousness and we illustrate its connections with a variety of diagnoses. Making use of the viewpoints distinguished by Jean-Paul Sartre: states, functions, qualities and structure, we give a new impulse to the study of consciousness disorders and offer a framework that provides a tool to understand consciousness, refine diagnostics and guide the development of therapeutic possibilities in clinical practice.